PENGARUH CARA PENGERINGAN TERHADAP AKTIVITAS MAKANDAN DAYA DAYA HIDUP RAYAP KAYU KERING CRYPTOTERMES CYNOCEPHALUS LIGHT - Agus Ismanto; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
This paper is dealing with the influence of drying methods to feeding activity and survival of Cryptotermes cynoce- phalus drywood termite. The result shows that drying methods have an effect on feeding activity and survival of C. cynocephalus. Besides the drying methods, wood species has also an effect on such both factor. The oven method is more advantageorus than desicator method which is more selective and more practice.